International Monetary Fund Administrative Tribunal Reports, Volume II, 2000-2002. (International Monetary Fund, 2009)
This paper discusses that during 2000-2002, the Tribunal considered a number of issues of substantive law upon which it had not previously been called upon to rule. These included interpretation of a provision of the IMF's Staff Retirement Plan that permits the IMF, pursuant to specified procedures, to give effect to orders for family support and division of marital property issued by domestic courts. Having the benefit of the extensive pleadings of all three parties, the Tribunal rendered a decision resolving the merits of the dispute. The Tribunal considered the evidence offered by the IMF in support of the differential in benefits between the two categories of staff and concluded that the distinction was rationally related to the purposes of the employment benefits at issue. Tribunal also grappled during 2000-2002 with the complexities of its relationship to other elements of the IMF's dispute resolution system. The IMFAT addressed the question of the admissibility before the Tribunal of an Application following dismissal of the complaint as untimely by the IMF's Grievance Committee.